2010
DOI: 10.4049/jimmunol.1000105
|View full text |Cite
|
Sign up to set email alerts
|

Inflammasome Activation by Adenylate Cyclase Toxin Directs Th17 Responses and Protection against Bordetella pertussis

Abstract: Inflammasome-mediated IL-1β production is central to the innate immune defects that give rise to certain autoinflammatory diseases and may also be associated with the generation of IL-17–producing CD4+ T (Th17) cells that mediate autoimmunity. However, the role of the inflammasome in driving adaptive immunity to infection has not been addressed. In this article, we demonstrate that inflammasome-mediated IL-1β plays a critical role in promoting Ag-specific Th17 cells and in generating protective immunity agains… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
162
1
11

Year Published

2011
2011
2017
2017

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 158 publications
(179 citation statements)
references
References 46 publications
5
162
1
11
Order By: Relevance
“…This finding is in accordance with the pattern of immune responses induced by CyaA, which activates both Th1-polarized CD4 + T cells and CTL responses (3,4). In agreement with our results, it recently has been reported that CyaA induced robust IL-1 production by DCs through the activation of caspase-1 and the NALP3-containing inflammasome complex (27). Although it has been shown that IL-1 and inflammasome could be important factors in the induction of T cell responses (23,28), the capacity of CyaA-OVA to trigger CTL responses was not affected in mice deficient in IL-1R or inflammasome components, clearly demonstrating that IL-1b and the inflammasome were not involved in the induction of the CTL response by the CyaA vector.…”
Section: Discussionsupporting
confidence: 82%
“…This finding is in accordance with the pattern of immune responses induced by CyaA, which activates both Th1-polarized CD4 + T cells and CTL responses (3,4). In agreement with our results, it recently has been reported that CyaA induced robust IL-1 production by DCs through the activation of caspase-1 and the NALP3-containing inflammasome complex (27). Although it has been shown that IL-1 and inflammasome could be important factors in the induction of T cell responses (23,28), the capacity of CyaA-OVA to trigger CTL responses was not affected in mice deficient in IL-1R or inflammasome components, clearly demonstrating that IL-1b and the inflammasome were not involved in the induction of the CTL response by the CyaA vector.…”
Section: Discussionsupporting
confidence: 82%
“…10C). Control nonimmunized Il17 2/2 mice had a higher bacterial burden than WT mice, which is consistent with the role of IL-17 in natural and whole-cell vaccine-induced immunity to B. pertussis (31,34). Immunization of WT mice, with Pa and LT as the adjuvant, significantly reduced the bacterial burden in the lungs of infected mice at day 5, with almost undetectable CFU by day 10.…”
Section: /2supporting
confidence: 60%
“…Indeed, unlike several PRR, the NLR protein family senses microbial molecules intracellularly in the cytosol [42][43][44][45][46]. This mechanism has been described for some viral and bacterial proteins [47][48][49] and for some adjuvants such as aluminum salts [39]. Since the inhibition of Sap internalization via the clathrin-dependent pathway results in a consistent inhibition of IL-1β and IL-18, it can be concluded that Saps must reach the cytoplasmic compartment to induce inflammasome activation.…”
mentioning
confidence: 99%